Milk and money - Schmedders, Karl, (SAGE knowledge. Cases., 2016)
The financial success of dairy farms depends critically on the price of their main output, milk. Large volatility in the price of milk poses a considerable business risk to dairy farms. This is particularly true for family-run dairy farms. The question then arises: how can a farm owner hedge the milk price risk? This case examines the viable options open for farmers and milk producers.